Phytochemical composition and toxicity assessment of Ammi majus L. - El-Guourrami, Otman; Salhi, Najoua; Fatima, Zahra; Zengin, Gokhan; Yilmaz, Mustafa Abdullah; Ameggouz, Mouna; Zahidi, Ahmed; Rouas, Lamiaa; Bouyahya, Abdelhakim; Goh, Khang Wen; Sam, Toong Hai; Long, Chiau Ming *; et al. (Elsevier, 2023)
Objective: To assess the acute and subacute toxicity as well as the phytochemical composition of two extracts and three fractions of Ammi majus L.